Correlation Between Vitamin D Deficiency and Calcium, Phosphorus, Alkaline Phosphatase in Preterm Libyan Infants: Case-Control study - Abad, Fatma; Eman Slouma, (AlQalam Journal of Medical and Applied Sciences, 2024)
Vitamin D plays a vital role in regulating calcium and phosphorus levels and in bone mineralization. Vitamin D deficiency is a widespread issue contributing to metabolic bone disease in preterm infants. This study aimed to evaluate the biochemical parameters associated with varying levels of vitamin D deficiency. Serum samples were collected from preterm infants at the Neonatal Intensive Care Unit of Althawra Hospital Center, Al Beyda, Libya, from Feb-July 2019. The study included two groups: 62 preterm infants and a control group of 34 full-term infants. Serum levels of calcium, phosphorus, alkaline phosphatase, and 25OH-Vitamin D were measured using enzyme immunoassays and standard method. The study involved 62 preterm neonates, with a median gestational age of 32 weeks (range 28-36) and median birth weight of 1960 gm (range 900-2800 gm). The median levels recorded were calcium at 8.7 mg/dl (p=0.000), phosphorus at 4.1 mg/dl (p=0.584), ALP at 458 U/L (p=0.008), and vitamin D at 13.6 ng/ml. The prevalence of varying degrees of vitamin D deficiency was noted: very severe (9.7% < 5 ng/ml), severe (19.4% 5-10 ng/ml), and overall deficiency (45% 10-20 ng/ml), and suboptimal (25.8% 20-30 ng/ml). Comparing preterm infants to the control group revealed statistically significant differences across all parameters (Vitamin D p=0.000, Ca p=0.007, PO4 p=0.036, and ALP p=0.000). All preterm infants exhibited inadequate vitamin D levels, and there was an inverse relationship between the biochemical parameters and vitamin D deficiency. Notably, the elevated ALP level could serve as a crucial marker for diagnosing vitamin D deficiency in clinical settings. يلعب فيتامين د دورًا حيويًا في تنظيم مستويات الكالسيوم والفوسفور وفي تمعدن العظام. يعد نقص فيتامين د مشكلة واسعة النطاق تساهم في أمراض العظام الأيضية عند الأطفال الخدج. تهدف هذه الدراسة إلى تقييم المعايير الكيميائية الحيوية المرتبطة بمستويات متفاوتة من نقص فيتامين د. طُرق تم جمع عينات مصل من الأطفال الخدج في وحدة العناية المركزة لحديثي الولادة بمركز مستشفى الثورة، البيضاء، ليبيا، من فبراير إلى يوليو 2019. شملت الدراسة مجموعتين: 62 طفلًا خديجًا ومجموعة ضابطة مكونة من 34 طفلًا مكتمل النمو. تم قياس مستويات الكالسيوم والفوسفور والفوسفاتيز القلوي (ALP) وفيتامين د 25OH في المصل باستخدام اختبارات المناعة الإنزيمية والطرق القياسية. نتائج شملت الدراسة 62 من حديثي الولادة الخدج، بمتوسط عمر حملي 32 أسبوعًا (نطاق 28-36) ومتوسط وزن عند الولادة 1960 جرامًا (نطاق 900-2800 جرام). كانت المستويات المتوسطة المسجلة هي الكالسيوم عند 8.7 مجم / ديسيلتر (قيمة P = 0.000)، والفوسفور عند 4.1 مجم / ديسيلتر (قيمة P = 0.584)، وALP عند 458 وحدة / لتر (قيمة P = 0.008)، وفيتامين د عند 13.6 نانوجرام / مل. لوحظ انتشار درجات متفاوتة من نقص فيتامين د: شديد جدًا (9.7٪ < 5 نانوجرام / مل)، وشديد (19.4٪ 5-10 نانوجرام / مل)، ونقص عام (45٪ 10-20 نانوجرام / مل)، ودون المستوى الأمثل (25.8٪ 20-30 نانوجرام / مل). أظهرت مقارنة الأطفال الخدج بمجموعة التحكم فروقًا ذات دلالة إحصائية عبر جميع المعلمات (فيتامين د ص = 0.000، الكالسيوم ص = 0.007، PO4 ص = 0.036، والفوسفاتيز القلوية ص = 0.000). خاتمة أظهر جميع الأطفال الخدج مستويات غير كافية من فيتامين د، وكانت هناك علاقة عكسية بين المعايير الكيميائية الحيوية ونقص فيتامين د. والجدير بالذكر أن مستوى ALP المرتفع يمكن أن يكون بمثابة علامة حاسمة لتشخيص نقص فيتامين د في الإعدادات السريرية